Intercomparison of polar ozone profiles by IASI/MetOp sounder with 2010 Concordiasi ozonesonde observations - Gazeaux, Julien; Clerbaux, Cathy; George, Maya; Hadji-Lazaro, Juliette; Kuttippurath, Jayanarayanan; Coheur, Pierre-François; Hurtmans, D.; Deshler, T.; Kovilakam, M.; Campbell, P.; Guidard, V.; Rabier, F.; et al. (Atmospheric Measurement Techniques, 2013)
Validation of ozone profiles measured from a nadir looking satellite instrument over Antarctica is a challenging task due to differences in their height sensitivity with ozonesonde measurements. In this paper we compare the ozone observations provided by the Infrared Atmospheric Sounding Interferometer (IASI) instrument onboard the polar-orbiting satellite MetOp with ozone profiles collected between August and October 2010 at McMurdo Station, Antarctica, during the Concordiasi campaign. This campaign was aimed at satellite data validation and up to 20 zero-pressure sounding balloons carrying ozonesondes were launched during this period when the MetOp satellite was passing above McMurdo. This makes the dataset relevant for comparison, especially because those balloons covered the entire altitude range of IASI profiles. The validation methodology and the collocation criteria differ according to the availability of Global Positioning System auxiliary data with each Electro-Chemical Cell ozonesonde observation. We show that the relative mean difference depends on the altitude range investigated. The analysis shows a good agreement in the troposphere (below 10 km) and middle stratosphere (25-40 km), where the differences are lower than 10%. However a significant positive bias of about 10-26% is estimated in the lower stratosphere at 10-25 km, depending on altitude. The positive bias in the 10-25 km range is consistent with previously reported studies comparing in-situ data with thermal infrared satellite measurements. This study allows a better characterization of the IASI products over the polar region when ozone depletion/recovery is occurring.